Photocatalytic Efficiency of Titanium Dioxide for Dyes and Heavy Metals Removal from Wastewater - Suresh Sagadevan; Is Fatimah; Titus Chinedu Egbosiuba; Solhe F. Alshahateet; J. Anita Lett; Getu Kassegn Weldegebrieal; Minh-Vien Le; Mohd Rafie Johan (Bulletin of Chemical Reaction Engineering & Catalysis, 2022)
The hazardous toxicity of dye materials, even in low concentrations, harms ecological systems. It releases a large number of contaminants into the water, resulting as waste water. Dyes prevent the process of photosynthesis by obstructing light passage, lowers the oxygen levels dissolved in the water. Also, a good number of the dyes and heavy metals are carcinogenic and mutagenic to human beings. Heterogeneous photocatalysis is a promising technology for removing organic, inorganic, and microbial pollutants from water and wastewater. It is preferable to other conventional wastewater treatment approaches due to its benefit, such as low cost, environmental friendliness, ability to proceed at ambient temperature and pressure conditions, and to completely degrade pollutants into environmentally safe products with suitable measures. The titanium oxide (TiO2) is one of the most promising material that has gained enormous importance in the field of energy and environmental applications. The unique physicochemical properties of TiO2 make it one of the best candidates among existing photocatalysts. This review provides an overview of strategies employed to augment its catalytic performance as well as the impact of different operational parameters on the removal proficiency of various organic and inorganic pollutants in water and wastewater treatment. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).